Expression of Multidrug and Toxic Compound Extrusion (MATE) Genes in Response to the Presence of Arsenic in Irrigation Water and Soil in Rice (Oryza sativa L.) - Debnath, S.; Bhattacharyya, S.; Sarkar, S.; Chatterjee, M. (International Journal of Bio-resource and Stress Management, 2023)
The problem of arsenic in diet through rice is going to be a great challenge in the coming days especially in India and Bangladesh. Several management technologies have already been recommended to encounter the problem of arsenic in crops and thereby in daily diet. In this regard, plant’s inbuilt defense mechanism may be utilized here. Likewise, to mitigate the issue, toxic compound extrusion genes are needed to be studied in detail. These genes play an important role in the detoxification of secondary metabolites, including alkaloids. So, we investigated the response of different Multidrug and toxic compound extrusion (MATE) genes in straw and grain of rice challenged to the presence of arsenic in irrigation water and soil. Relative expression of Multidrug and toxic compound extrusion transporter genes located on chromosome 3, 5, 10 and 12 were measured in two contrasting rice genotypes. These genes were assumed to be arsenic responsive as expression of all these genes in Satika (low accumulator) was higher than that of TN 1 (high accumulator) in control condition and expression increased significantly in both the genotypes when arsenic was present in soil. Particularly, LOC_Os05g48040 might have some role in sequestration of arsenic in stem and thus reducing arsenic in grain revealed through validation in rice genotypes contrasting for arsenic accumulation. This gene may play a pivotal role to understand the route of arsenic detoxification in rice and thereby develop a breeding strategy.